Bentuk Tradisi Penjagaan Al-Qur’an Lewat Khataman Al-Qur’an Via Whatsapp Oleh Organisasi Tanaszaha Muslimat Cabang Situbondo - Nabawiyah, Habsatun (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2023)
This study examines the tradition of khataman al-Qur'an through WhatsApp media by the Tanaszaha Muslimat organization, Situbondo Branch. The focus of this research is to find out the procession of the implementation and meaning of the Khataman al-Qur'an which is carried out every week by members of the WhatsApp group Tanaszaha Muslimat Situbondo Branch. This research is descriptive in nature, namely systematically explaining the practices of living the Qur'an on members of the WhatsApp group Tanaszaha Muslimat Situbondo Branch. Data collection methods used in this research are observation or observations, in-depth interviews or interviews, and documentation. In this study using the sociological theory offered by Karl Mannheim. The results of this study can be concluded that the time and procession of khataman al-Qur'an through the WhatsApp media starts on Friday until it is finished on Thursday afternoon at the latest. This Khataman begins with tawassul in the form of reciting surah al-Fatihah then proceed with reading the Koran. Based on Karl Mannheim's sociological theory, three categories of meaning are found; The meaning of the purpose of khataman al-Qur'an through WhatsApp is a form of ta'dhiman (respect; glorify) to teachers. On the expressive meaning, that the activity of completing the Al-Qur'an is to get a reward from reading the Qur'an, blessings from the teachers, and encouraging to be istiqomah in reciting the Koran. While the meaning of the documentary, khataman al-Qur'an through WhatsApp media is to get rewards and blessings from reading the al-Qur’an.